2D:4D Is Negatively Associated to Aggressive Dominance in Men: A Response to Voracek (2013). Issue 2 (5th February 2013) - van der Meij, Leander; Almela, Mercedes; Buunk, Abraham P.; Dubbs, Shelli; Salvador, Alicia
Abstract We do not agree with the interpretation and evaluation of our article by Voracek. We feel that our results and our interpretation of the results are supported by our data analyses and do add to the current understanding of the relationship between 2D:4D and personality. We feel confident we can address many, if not all, of Voracek's criticisms. However, we fully agree that 2D:4D research would benefit from more replication and from the use of larger sample sizes. Aggr. Behav. 39:88–89, 2013. © 2013 Wiley Periodicals, Inc.